UPAYA PENINGKATAN RASA PERCAYA DIRI SISWA DI PANTI ASUHAN AUR PAKAN KAMIS - Ema Tami Lestari; Dodi Pasilaputra (CV. ADIBA AISHA AMIRA, 2024)
The background of this research is the discovery of self-confidence problems in children at the Panti Asuhan Aur Pakan Kamis, which are characterized by a sense of shame in expressing opinions and appearing in public. This study aims to determine the efforts to increase the self-confidence of children at the Panti Asuhan Aur Pakan Kamis. This research is a qualitative research using a phenomenological approach. Collecting data in this study is through observation. The results showed that many children at the Panti Asuhan Aur Pakan Kamis had less than optimal self-confidence, so self-development was needed through one of the guidance and counseling services.